2020
DOI: 10.1177/1938965520943094
|View full text |Cite
|
Sign up to set email alerts
|

Response Rates In Hospitality Research: An Overview of Current Practice and Suggestions For Future Research

Abstract: In this paper, we examine published research in six top-tier hospitality journals to explore response rates for different survey distribution methods across specific characteristics like research context, respondents, and geographical regions. Data were analyzed from 1,389 papers published from January 2001 to December 2019. By looking at a large set of published response rates, distribution and enhancing methods and type of respondents, findings from this study will aid researchers in designing more effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…A total of 850 questionnaires were distributed, out of which 410 questionnaires were returned. Upon careful screening, 372 questionnaires were deemed useable for data analysis, which is in line with average response rates in hospitality research involving employees ( Ali et al, 2020 ).…”
Section: Methodsmentioning
confidence: 90%
“…A total of 850 questionnaires were distributed, out of which 410 questionnaires were returned. Upon careful screening, 372 questionnaires were deemed useable for data analysis, which is in line with average response rates in hospitality research involving employees ( Ali et al, 2020 ).…”
Section: Methodsmentioning
confidence: 90%
“…Laguilles et al (2011) and Cobanoglu and Cobanoglu (2003) have highlighted the effectiveness of lotteries in increasing response rates. Follow‐ups were also used to increase the survey response rate (Ali et al, 2020). Of the 411 responses, seven had to be dropped due to missing data.…”
Section: Methodsmentioning
confidence: 99%
“…However, this research showed that environmental responsibility worked as a nonsignificant attribute for purchase intention, indicating that the environmental element is not critical for sales growth in the context of café businesses. It is possible that either an indirect path toward a certain attribute (e.g., trust, risk, and value) for the environmental element or other specific green areas (e.g., labeling, organic sourcing, or packaging) might determine purchase intention significantly in the coffee shop business domain, as previous research has addressed [58][59][60][61]66]. This implies that more in-depth investigation of the environmental responsibility is necessary to consider more diverse paths and variables.…”
Section: Explanation For the Hypotheses Testingmentioning
confidence: 99%